The Oxford handbook of regulation - Baldwin, Robert, 1951-; Cave, Martin.; Lodge, Martin, 1972- (Oxford handbooks in business and management., 2010)
This handbook provides a discussion the major trends and issues in regulation over the last 30 years, together with an outline of prospective developments. Each chapter offers a broad overview of key current issues and provides an analysis of different perspectives on those issues.